(3GSJjYGH GdhLhg GdeecfI aj UfYI GdESWQdGHs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3SYO Hf YHO GdZaGQ Hf fUQ Hf YHO GdcQje Hf eMeO GdNWHi GdeTcGfi s)
(3ChdgG (B:s
(3hHYO , aEf GdHjQhfi jbhd (B: (3gPG cJGH ai ESJjYGH GdhLhg GdeecfI ai UfYI GdCSWQdGH EYde Cf GdCfaS GdUGajI PhGJ fRhY hGTJjGb Edi JUhQ GdehLhOGJ HGdEMGWI HgG HEWdGb s
(3BNQgG (B:s
(3eSJNQL GdUaMI GdBaGbjI , hhUdfG cd hGMOI ef Jdc GdbWY MJi Jchf GdYQhV cKjQI , hjchf CMSf ai GdUhQI hbGQHJ Cf JYe GdYQhV ai GdYed hHJeGe gPg GdBdI EfLGR GdhYO Ydi eG hYOJg , hGdhaGA HeG VefJg Je cJGH s
(3HgG fXGe GdJYbjHIs
(3HgG CTcGd hLOGhds
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs